2014
DOI: 10.1002/asia.201402196
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport Characteristics of the Dimeric 1,4‐Benzenedithiol Junction

Abstract: Understanding the electron transport between single molecules connected through weak interaction is of great importance for molecular electronics. In this paper, we report measurements of the conductivity of the dimeric 1,4-benzenedithiol (BDT) junction using the scanning tunneling microscopy (STM)-based current-displacement I(s) method. The conductance was measured to be 6.14×10(-6)  G0 , a value almost two orders of magnitude lower than that of the monomer BDT junction. In control experiments, the probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Under ambient conditions, it has been demonstrated that BDT can convert to dimeric-BDT spontaneously as a result of oxidative dimerization. 41 We estimated the effective conductive length of a dimeric-BDT molecule through density functional theory (DFT) calculation. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Under ambient conditions, it has been demonstrated that BDT can convert to dimeric-BDT spontaneously as a result of oxidative dimerization. 41 We estimated the effective conductive length of a dimeric-BDT molecule through density functional theory (DFT) calculation. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Figure S2, PT is much less effective at protecting the surface from oxidation than PDT. Alkanedithiols can polymerize spontaneously in vapor; , hence, the reason that PDT is so effective in preventing oxidization may be that it forms a relatively thick layer on adsorption because of polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Benzene-1,4-dithiol (M0) is considered as a good example to investigate electron transport and functionality of molecular junctions in the field of organic electronics. Both experiment [1][2][3][4] and theory [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been interested in reporting and understanding electron transport properties of M0 and its derivatives. For instance, Reed et al, 1 measured the I-V characteristics of M0 using the mechanically controllable break junction.…”
Section: Introductionmentioning
confidence: 99%
“…The non-equilibrium Green functions combined with the density functional theory (NEGF-DFT) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] reported electron transport through M0 with regard to its structures and derivatives, nature of electrode and anchors. Seminario et al, 5 studied the effect of electrode nature on conductance of M0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation